Effect of carbon nanotube-silane addition on mechanical properties of chloroprene rubber-filled carbon black / Kok-Tee Lau...[et al.] - Kok, Tee Lau; Abd Razak, Jeefferie; Ab Maulod, Hairul Effendy; Muhamad, Noraiham; Hashim, Mohamad Hanif; Mohd Saad, Nurzallia (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Chloroprene-filled CNT rubber has been investigated for the electromagnetic shielding application. Nevertheless, there are continuous studies to overcome CNTs agglomeration, materials loss and air contamination issues generated during conventional melt compounding process. Thus, the current study proposes the usage of polar and low molecular weight ethanol solvent as dispersant for CNT fillers and silane-based Si-69 as coupling agent. Si-69 is a widely used fillers' coupling agent because of its reliable performance in the industrial-scaled rubber compounding process. This study is to investigate the effect of carbon nanotube (CNT)-Silane addition as secondary fillers on tensile strength, elastic modulus and cure characteristics of hloroprene rubber (CR)- filled carbon black (CB) compound. The CR-filled CB was prepared by internal mixing, followed by roll-mill process in which CNT-Silane dispersion was added. For comparison, the samples of CR-filled CB without CNTs addition and with as-received CNTs addition were prepared and characterized. The CR composite added with CNT-Silane dispersion displayed tensile strength and elastic modulus (at 300% elongation) of 23 MPa and 18 MPa respectively, which are 4% higher than the CR composite added with asreceived CNTs. The findings were supported by the FESEM micrograph of tensile fracture samples that showed the CNT-Silane addition produced better CNTs dispersion in the CR-filled CB compound. Furthermore, the usage of CNT-Silane improved the CR-filled CB compound processibility by reducing the minimum (ML) and maximum torque (MH) values from 0.34 and 1.11 N.m in as-received CNT samples to 0.32 and 1.04 N.m respectively in CNT-silane samples.